Demographic, procedural and 30-day safety results from the WEB Intra-saccular Therapy Study (WEB-IT). (17th January 2017) - Fiorella, David; Molyneux, Andrew; Coon, Alexander; Szikora, Istvan; Saatci, Isil; Baltacioglu, Feyyaz; Sultan, Ali; Arthur, Adam
Abstract : Introduction: The Woven EndoBridge (WEB) represents a novel intrasaccular therapeutic option for the treatment of intracranial wide-necked bifurcation aneurysms (WNBAs). The WEB-IT Study is a pivotal Investigational Device Exemption (IDE) study to determine the safety and effectiveness of the WEB device for the treatment of WNBAs located in the anterior and posterior intracranial circulations. We present the patient demographics, procedural characteristics, and 30-day adverse event data for the US WEB-IT study. Methods: WEB-IT is a prospective multicenter single-arm interventional study conducted at 25 US and 6 international centers. The study enrolled 150 adults with WNBAs of the anterior and posterior intracranial circulations. All patients were intended to receive a WEB device delivered via standard endovascular neurosurgical embolization techniques. The study was conducted under Good Clinical Practices and included independent adjudication effectiveness outcomes and all adverse events. Results: One hundred and fifty patients enrolled at 27 investigational sites underwent attempted treatment with the WEB. Mean age was 59 years (range 29–79) and 110 (73.3%) of the patients were female. Treated aneurysms were located at the basilar apex (n=59, 39.3%), middle cerebral artery bifurcation (n=45, 30%), anterior communicating artery (n=40, 26.7%), and internal carotid artery terminus (n=6, 4%). Average aneurysm size was 6.4 mm (range 3.6–11.4) with a mean neck size of 4.8 mm (range 2.0–8.2, mean dome to neck ratio 1.34). Nine patients presented with ruptured aneurysms. Of the enrolled patients, 98.7% were treated successfully with WEB devices. Mean±SD fluoroscopy time was 30.2±15.7 min. One primary safety event (PSE) (0.7%)—a delayed parenchymal hemorrhage 22 days after treatment—occurred between the index procedure and 30-day follow-up. In addition to the single PSE, there were seven (4.7%) minor ischemic strokes (5 resolved without sequelae and 2 had a modified Rankin Scale score of 1 at 30 days), five (2.7%) transient ischemic attacks, and two (1.3%) minor subarachnoid hemorrhages, which did not meet the prospectively established criteria for PSEs. Conclusions: The WEB device can be used to treat WNBAs with a high level of procedural safety and a high degree of technical success. Trial registration number: NCT02191618; Pre-results.